Compositional analysis of soybean event IND-ØØ41Ø-5 - Chiozza, Mariana V. (2020)
Soybean (Glycine max L.) is the world’s largest source of protein feed and the second largest source of vegetable oil. Water restriction is the main limiting factor to achieve maximum soybean yields. Therefore, development of varieties that maintain yield under environmental stresses is a major objective of soybean breeding programs. The HaHB4 (Helianthus annuus homeobox 4) gene from sunflower encodes for a transcription factor involved in the plant´s tolerance to environmental stress. The introduction of HaHB4 in soybean led to the development of event IND-ØØ41Ø-5 (HB4® soybean), which displayed higher yield in environments having low productivity potential, compared with the parental control variety. Compositional analyses of soybean event IND-ØØ41Ø-5 were conducted both in Argentina and the United Sates. A total of 44 components were analyzed in grain and 9 components in forage. Based on the results of these studies it was concluded that soybean event IND-ØØ41Ø-5 was compositionally equivalent to its non-transgenic parental control.